Analisis Termogravimetri dan Dekomposisi Termal pada Produksi Bio-Oil dari Daun Tebu Menggunakan Proses Pirolisis Cepat - Ilham Mufandi; Ratchaphon Suntivarakorn; Wasakorn Treedet; Piyapong Singbua (Eksergi, 2023)
Sugarcane leaves are one of the agro-industrial wastes derived from sugarcane plants. In this research, sugarcane leaves are used as raw material for pyrolysis which produces three main products: liquid, solid, and gas. The focus of this research is to identify the effect of temperature on pyrolysis, identify mass changes, identify decomposition, and identify the chemical composition of bio-oil. The pyrolysis was carried out using a Circulating Fluidized Bed (CFBr) reactor with pyrolysis temperature variations from 440oC to 520oC. Analysis of pyrolysis characteristics of sugarcane leaves are used thermogravimetric analysis (TGA), DTA, and GC-MS analysis. The results showed that the operating temperature had a significant effect on the pyrolysis process. The highest bio-oil found at 480oC, namely 34.33%. TGA results show that the decomposition process of sugarcane leaves is divided into 3 stages: 1) dehydration of water content occurs at <200oC, 2) active pyrolysis occurs from 200oC to 380oC, and 3) passive pyrolysis occurs at temperature from 380oC to 500oC. DTA results show that the thermal changes are affected by the pyrolysis heating rate. The highest bio-oil compounds are Î²-D-Glucopyranose 1,6-anhydro, acetic acid, and 2-Propanone 1-hydroxy-. This research proves that temperature has an important role in the pyrolysis process.